The Role of Human Factors and Ergonomics Professionals on Sustainable Development - dos Santos, Eduardo Ferro; de Oliveira, Karine Borges [UNESP]; Martinez, Gustavo Aristides Santana; Silva, Messias Borges (Springer Nature, 2020)
Sustainable development goals (SDG) have been proposed by Agenda 2030 (UN), and challenges relate to the application of the triple bottom line (TBL) - people, planet, and profit. Human factors and ergonomics (HFE) professionals develop actions integrating an equal TBL – health (people), safety (planet), and performance (profit). The issue of sustainable development has become one of the main priorities all over the world, and to establish projects by HFE professionals to collaborate for SDG goals is essential. The SDG is a relatively young area of research, and the main purpose of this study is to identify actions, projects, gaps, and trends in the literature integrating HFE and SGD. A bibliometric analysis explored the Scopus database, examining documents from 1999 to 2019. The results suggest that HFE professionals still have a long way to produce more research about SGD. We must act to raise awareness among HFE professionals. These actions will be established new researches and projects related to sustainability and collaborate with Agenda 2030.
Keywords: Agenda 2030; Sustainability; Sustainable development